2018
DOI: 10.3390/ijms19030735
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ion Transport in the Intestine by Free Fatty Acid Receptor 2 and 3: Possible Involvement of the Diffuse Chemosensory System

Abstract: The diffuse chemosensory system (DCS) is well developed in the apparatuses of endodermal origin like gastrointestinal (GI) tract. The primary function of the GI tract is the extraction of nutrients from the diet. Therefore, the GI tract must possess an efficient surveillance system that continuously monitors the luminal contents for beneficial or harmful compounds. Recent studies have shown that specialized cells in the intestinal lining can sense changes in the luminal content. The chemosensory cells in the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
1
4
0
Order By: Relevance
“…sMCT1 is a Na + -coupled transporter expressed solely on the apical membrane of the colonic epithelium that mediates SCFA influx from the lumen (Ritzhaupt et al, 1998;Kuwahara et al, 2018). The western blot results showed that the expression level of sMCT1 did not change in IHLD rats compared to the control rats, as shown in Figure 7A, consistent with the immunofluorescence results ( Figures 7G,H).…”
Section: Expression and Location Of Mct And Smct1 In The Colon Of Thesupporting
confidence: 83%
See 2 more Smart Citations
“…sMCT1 is a Na + -coupled transporter expressed solely on the apical membrane of the colonic epithelium that mediates SCFA influx from the lumen (Ritzhaupt et al, 1998;Kuwahara et al, 2018). The western blot results showed that the expression level of sMCT1 did not change in IHLD rats compared to the control rats, as shown in Figure 7A, consistent with the immunofluorescence results ( Figures 7G,H).…”
Section: Expression and Location Of Mct And Smct1 In The Colon Of Thesupporting
confidence: 83%
“…Currently, there is growing evidence indicating that SCFAs are a product of bacterial fermentation involved in the regulation of ion transport (Yajima et al, 2011;Tan et al, 2014;Kuwahara et al, 2018). Previous studies demonstrated that luminal addition of propionate stimulates chloride secretion, which function as a lubricant for the movement of luminal contents in the colon (Yajima et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bodily and cellular functions are controlled by various factors including ions such as Na + , K + , Ca 2+ , Mg 2+ , Zn 2+ , and Cl − [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ]. On the one hand, pH (−log[H + ]) is recognized as one of classical items considered to be already fully understood in roles and mechanisms of homeostasis.…”
Section: Variety Of the Interstitial Fluid Phmentioning
confidence: 99%
“…To confirm each role of SMCT1/SMCT2 in efficient monocarboxylate absorption, we have to perform further studies. A growing body of evidence indicates that the gut microbiota exerts important influences on the physiology of their mammalian host by signaling through metabolic byproducts such as short-chain fatty acids (SCFAs) which enter the bloodstream via colonic absorption (Samuel et al 2008;Maslowski et al 2009;Kuwahara et al 2018;Kuwahara et al 2019;Kuwahara et al 2020). Most of SCFAs are acetate, propionate and butyrate, which account for > 95% be caused by low affinity of insulin to its receptor due to much lower pH values of the interstitial fluid than arterial blood pH (Aoi et al 2013;Marunaka 2021).…”
Section: Discussionmentioning
confidence: 99%